2007
DOI: 10.1089/ten.2006.0015
|View full text |Cite
|
Sign up to set email alerts
|

The Cytocompatibility and Early Osteogenic Characteristics of an Injectable Calcium Phosphate Cement

Abstract: In this study, the cytocompatibility and early osteogenic characteristics of rat bone marrow cells (RBMCs) on injectable calcium phosphate (CaP) cement (Calcibon) were investigated. In addition to unmodified CaP cement discs, 2 other treatments were given to the discs: preincubation in MilliQ and sintering at different temperatures. After primary culture, RBMCs were dropwise seeded on the discs and cultured for 12 days. The samples were evaluated in terms of cell viability, morphology (live and dead assays and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 43 publications
6
38
1
4
Order By: Relevance
“…However, it is worth noting that in the direct contact studies all cements and foams showed cell proliferation rates lower than that observed on the control TCPS. This result is coincident with previous studies on apatitebased ceramics and cements [5,[35][36][37][38][39]. It can be hypothesised that the relatively rougher surface topography of the cements may affect cell behaviour, directing cells towards a more differentiated phenotype rather than towards a proliferative one [40].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is worth noting that in the direct contact studies all cements and foams showed cell proliferation rates lower than that observed on the control TCPS. This result is coincident with previous studies on apatitebased ceramics and cements [5,[35][36][37][38][39]. It can be hypothesised that the relatively rougher surface topography of the cements may affect cell behaviour, directing cells towards a more differentiated phenotype rather than towards a proliferative one [40].…”
Section: Discussionsupporting
confidence: 90%
“…Currently, numerous synthetic scaffolds have been designed to favour cell attachment, cell growth and cell differentiation [3,4]. Some of the crucial characteristics of scaffolds are porosity and pore interconnectivity, which are necessary to allow tissue in-growth [5]. The ideal porosity of a scaffold should lie within a critical range to maintain its mechanical integrity, while undergoing resorption and sustaining cell proliferation and new extracellular matrix deposition [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…BoneSource Ò , composed of tetracalcium phosphate and dicalcium phosphate anhydrous, has a porosity of 46% [29,30] and a pore size of 2-50 lm [31]. Calcibon Ò consists of a-TCP, and has a porosity of 30-40% [32,33] with a pore size of <1 lm [33]. Calcibon Ò has a density of 1.84 g cm -3 [32], whereas Norian SRS Ò has a density of 1.3 g cm -3 [34].…”
Section: Structural Propertiesmentioning
confidence: 99%
“…[1][2][3][4] Since 1983, calcium phosphate cements (CPCs) have gained much attention and have been used as injectable bone substitutes [4][5][6][7][8] that can be injected into bone cavities or defects. However, it is difficult to deliver a CPC to a complicated site and to compact it adequately due to brittleness.…”
mentioning
confidence: 99%
“…Efforts have been made in recent years to overcome the disadvantages of these handling properties. Thus, several studies have focused on the addition of polymeric materials, such as chitosan, [9][10][11] alginate [3,7] and gelatin, [7,[12][13][14][15] into CPCs. Moreau and Xu [9] developed a fast-setting and anti-washout CPC-chitosan scaffold, with higher strength than the CPC control, in which chitosan lactate was mixed with water at a mass fraction of 15%.…”
mentioning
confidence: 99%